Estimasi Biomassa Karbon dan Serapan CO2 Ekuivalen Pohon Kemiri dan Kopi dalam Sistem Agroforestri di Kabupaten Buton - La Ode Midi; Sahindomi Bana; Nabilah Al Fadiyah Wahid Ode; Laode Sabaruddin; La Gandri; La Ode Muhammad Erif; Ema Hermawati Garusu; Surya Cipta Ramadhan Kete (Universitas Pattimura, 2026)
Agroforestry is a land-use system with the potential to increase biomass, carbon stock, and estimated CO₂-equivalent sequestration, thereby contributing to climate change mitigation. This study aimed to estimate aboveground biomass, carbon stock, and CO₂-equivalent sequestration in a candlenut (Aleurites moluccanus)–coffee (Coffea canephora) agroforestry system in Kaongkeongkea Village, Pasarwajo District, Buton Regency, Southeast Sulawesi. Field measurements were conducted from November to December 2024 using a non-destructive method by measuring diameter at breast height (DBH) in 11 plots measuring 20 m × 20 m, with a total sample area of 0.44 ha. Biomass was estimated using species-specific allometric equations, carbon stock was calculated using a carbon fraction of 47%, and CO₂-equivalent sequestration was estimated using a conversion factor of 3.67. The results showed that the agroforestry system was dominated by coffee, with a density of 215.91 trees ha⁻¹, while candlenut had a density of 113.64 trees ha⁻¹. The average biomass of candlenut reached 117.06 tons ha⁻¹, higher than that of coffee at 12.35 tons ha⁻¹. The carbon stock of candlenut was 55.02 tons C ha⁻¹, while coffee stored 5.81 tons C ha⁻¹. Meanwhile, CO₂-equivalent sequestration was 201.74 tons CO₂ ha⁻¹ for candlenut and 21.29 tons CO₂ ha⁻¹ for coffee. Across the 43 ha agroforestry area, total CO₂-equivalent sequestration was estimated at 9,589.97 tons CO₂. These findings indicate that candlenut contributes dominantly to carbon stock in the agroforestry system.